ECONOMIC GLOBALIZATION, ENTREPRENEURSHIP AND INCLUSIVE GROWTH IN AFRICAN OIL EXPORTING COUNTRIES - KEMNETI , KENNETH OLISE; OLALEKAN , BASHIR AWORINDE; OLUSEGUN , AJIBOLA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
Policymakers in developing nations espouse the objective of attaining expeditious and enduring economic expansion. This is because such expansion will provide individuals with a wide range of chances to be innovative and productive. The imperative for these policies to expedite growth is not unrelated to the elevated levels of unemployment, severe poverty, and widening inequality that have contributed to sluggish inclusive growth. In order to attain the requisite level of expansion, a renaissance in entrepreneurial endeavours and more extensive economic globalisation are required. The study investigated the impact of entrepreneurship and economic globalisation on the GDP per employed individual in oil-exporting African nations. The study employed an ex post facto research design. Participating in the study were sixteen oil-exporting African nations. Data were taken from the World Bank Development Indicators, the World Bank Entrepreneurship Survey, the KOF Globalization Index, the Worldwide Governance Indicators, the African Infrastructure Development Index, and the International Energy Agency for the sample period of 2006–2021. Using descriptive and inferential statistics, the data were analysed with a significance level of 5%. The study's purpose was specifically accomplished by the utilisation of a dynamic heterogeneous panel consisting of the following: pooled mean group, mean group, dynamic fixed effect, and augmented mean group. The study revealed that economic globalization and entrepreneurship significantly influenced GDP per person employed (Wald-test (6, 249) = 39.27, p < 0.05). The study concluded that economic globalization and entrepreneurship have a significant influence on GDP per person employed in the selected oil-exporting countries in Africa. The study recommends that that oil exporting African countries policy makers should implement policies that would encourage economic globalization and entrepreneurship so as to reap the benefits thereof. This is because economic globalization provides entrepreneurs access to new markets and promotes good quality and quantity of products